Production of bio-indigo dye by surmounting its physical and chemical insoluble nature - Yuk, Yong; Jang, Ji Hwan; Park, Seo A.; Park, Hyun A.; Ahn, Jung Oh; Yang, Yung Hun; Ham, Sion; Park, See Hyoung; Park, Kyungmoon; Kim, Su Young; Kim, Young Soo; Lee, Jeongchan; et al. (Dyes and Pigments, 2023)
Indigo is a natural blue dye that has been in use for centuries. However, its insolubility in water and most organic solvents limits its application in various fields. In this study, we aimed to enhance the indigo production by surmounting its physical and chemical insolubility. To achieve this, a combination of genetic engineering, biotransformation optimization, and solubilization techniques has been employed. First, the indole-converting enzymes, flavin-containing monooxygenase (MaFMO) from Methylophaga aminisulfidivorans and toluene monooxygenase from Pseudomonas mendocina (PmT4MO), were tested and their expression was optimized, which allowed for the efficient conversion of indole to indigo via indoxyl. Next, to overcome the insolubility of indigo and facilitate indole/indigo transport through the cell membrane, organic solvents and detergent mixing were optimized. Genetic modification was attempted by introducing caveolae complex structures into the membrane to create a permanent indole/indigo transport system. Finally, inspired by wastewater treatment and indigo solubilization during the indigo-dyeing process, indigo adsorption and reduction were applied using an Amberlite XAD4 adsorption bead and thiourea dioxide reducing agent to achieve enhanced production of indigo, respectively. These counteracting strategies against the insoluble nature of indigo resulted in a significant increase in bio-indigo production, with 1.5 g/L produced from 15 mM indole, representing an increase of more than 300% compared with that of the initial production titer. This study provides valuable insights into the optimization of indigo bioproduction and could lead to the development of more efficient methods for bio-dye production.
Keywords: Amberlite; Amberlite XAD4; Bio-indigo; Flavin containing monooxygenase; Indigo dye; Indole; Optimisations; Solubilisation; Thiourea dioxide; Toluene dioxygenase; Amberlite XAD4; Bio-indigo; Flavin-containing monooxygenase; Indole; Thiourea dioxide; Toluene dioxygenase